JURIDICIAL ANALYSIS OF ONLINE GENERAL DATA PROTECTION IN INDONESIA (International Conference of Graduate School on Sustainability (ICGSS), 2020)
This article discusses the urgency and need for general data protections and regulations in Indonesia. Remembering how important the value of personal data that has access to the user’s  finance account. There are many cases about data stolen from user accounts in recent years in so many e-commerces as data holder dan general data processor. On the other hand, millions users don’t have legal certainty about the accountability and protection of their rights since, to this date, there are no specific regulations controlling such things, only some unspecific and unclear articles scattered throughout many older regulations, such as “undang-undang ITE” (the regulation of electronical transaction) and many other government-made laws. This article uses the normative approach method to analyse the absence of these laws in Indonesia by referring not only to previous laws that this country already had but also regulations which were drafted and other country regulations. Using this method a legal plan about general data protection in Indonesia was found but the launch is always cancelled until this article written, even though in many developed countries such as European countries under the European Union already have the GDPR which stands for “General Data Protection Regulation”. This program is quite successful in field application. In the discussion section, it is recommended that Indonesia examine its own general data protection regulation, “Rancangan Undang-Undang Perlindungan Data Pribadi” by referring to European Union GDPR and enact this regulation as soon as possible, as it is greatly needed to protect individuals privacy rights. Keywords: Personal data abuse, General data protection, GDPR